Influence of Leadership Styles on Project Team Performance in Rwanda - Kaneza, Jean (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the influence of leadership styles on project team performance in Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study conducted on the influence of leadership styles on project team performance in Rwanda revealed several key findings. Firstly, it was observed that transformational leadership, characterized by inspirational motivation, intellectual stimulation, individualized consideration, and idealized influence, had a significantly positive impact on project team performance. Leaders who exhibited these qualities were able to inspire and motivate their teams, foster innovation and creativity, and demonstrate a strong commitment to achieving project goals, thereby enhancing overall performance. Additionally, transactional leadership, which involves the exchange of rewards and punishments for performance, was found to have a moderate positive effect on project team performance. However, this effect was not as strong as that of transformational leadership. Furthermore, the study also found that laissez-faire leadership, characterized by a hands-off approach and minimal involvement in decision-making, had a negative impact on project team performance. Overall, the findings underscore the importance of effective leadership in driving project success and highlight the need for leaders to adopt transformational and transactional leadership styles while avoiding laissez-faire leadership practices. Implications to Theory, Practice and Policy: Transformational leadership theory, contingency theory and social exchange theory may be use to anchor future studies on assessing the influence of leadership styles on project team performance in Rwanda. Organizations should invest in leadership development programs tailored to cultivate a diverse range of leadership styles among project leaders. Policy-makers should integrate leadership competencies into project management standards and guidelines.